2006
DOI: 10.1016/j.clpt.2006.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin alters the pharmacokinetics of bromocriptine by inhibition of organic anion transporting polypeptide C–mediated uptake

Abstract: reported that erythromycin significantly increased the area under the curve per kilogram of bromocriptine by 286%, and a 4.6-fold greater maximum plasma concentration than that observed with bromocriptine alone was found. In their report the caffeine-bromocriptine interaction was also studied, and no significant interaction was found. The interaction between erythromycin and bromocriptine is clinically significant. However, the mechanism is not known.Erythromycin is a well-known substrate and inhibitor of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The identification of bromocriptine as a new substrate of OATP1A2 and OATP2B1 was in line with a previous study demonstrating bromocriptine to be transported by OATP1B1. 45 While OATP1B1 shows a liver-specific expression profile and is therefore a candidate gene for systemic drug−drug interactions, OATP1A2 and OATP2B1 are expressed in different tissues including the BBB, 14 indicating a possible function in drug uptake to the brain. The brain expression of both transporters was supported by our LC− MS/MS results and immunofluorescence stainings.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The identification of bromocriptine as a new substrate of OATP1A2 and OATP2B1 was in line with a previous study demonstrating bromocriptine to be transported by OATP1B1. 45 While OATP1B1 shows a liver-specific expression profile and is therefore a candidate gene for systemic drug−drug interactions, OATP1A2 and OATP2B1 are expressed in different tissues including the BBB, 14 indicating a possible function in drug uptake to the brain. The brain expression of both transporters was supported by our LC− MS/MS results and immunofluorescence stainings.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This finding could be relevant for the prediction of potential drug-drug interactions. Octreotide, when administered concomitantly, has been shown to increase the bioavailability of the OATP1B1 substrate bromocriptine by 40% (Flogstad et al, 1994;Lu et al, 2006). Additionally, octreotide is rapidly cleared by the liver, suggesting an extensive first-pass elimination if administered orally and requiring much higher doses to achieve similar blood peak concentrations (C max ∼ 5 nM) (Tuvia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The potential importance of cytochrome genetic variability on the pharmacokinetics of dopamine agonists can be estimated from results obtained when they were co-administered with cytochrome inhibitors. For example, co-administration of cytochrome P450 3A4 (CYP3A4) inhibitors increases the area under curve of bromocriptine 22,23 or cabergoline plasma levels. 24,25 When patients are treated with ropinirole and a cytochrome P450 1A2 (CYP1A2) inhibitor such as ciprofloxacin, an increase in the AUC for ropinirole is observed 26 and it has been suggested that dose adjustments of ropinirole may be necessary when introducing or discontinuing a potent CYP1A2 inhibitor.…”
Section: Response To Dopamine Agonistsmentioning
confidence: 99%